2015
DOI: 10.7243/2055-091x-2-14
|View full text |Cite
|
Sign up to set email alerts
|

The potential protective effect of propolis on experimentally induced hepatitis in adult male albino rats. Histological and immunohistochemical study

Abstract: Background: In Egypt, liver diseases are one of the most prominent killers especially hepatitis virus infection, fibrosis and cirrhosis. Hepatitis has a serious health effects and alter the functions of the liver. D-galactosamine (D-GalN) and Lipopolysaccharide (LPS) induced hepatitis in rats are closely resembling human viral hepatitis. Propolis is honey bee product with a wide range of beneficial therapeutic effects. Objective: To evaluate the possible protective effect of propolis on experimentally induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
4
22
0
Order By: Relevance
“…El-Mahalaway et al (2015) demonstrated a potential protective effect of propolis against experimentally induced hepatotoxicity (via D-galactosamine (D-GalN)) and lipopolysaccharide (LPS) induced hepatitis in rats. The observed hepatoprotective effect of propolis was attributed to its strong antioxidant, anti-inflammatory, and antiapoptotic activities [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El-Mahalaway et al (2015) demonstrated a potential protective effect of propolis against experimentally induced hepatotoxicity (via D-galactosamine (D-GalN)) and lipopolysaccharide (LPS) induced hepatitis in rats. The observed hepatoprotective effect of propolis was attributed to its strong antioxidant, anti-inflammatory, and antiapoptotic activities [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The liver is a vital organ that plays a key role in the detoxification of exogenous and endogenous substances. It also performs a wide range of metabolic activities required for homeostasis, nutrition, and immune defense [ 13 ]. Subclinical infections are a major problem in broiler breeding and also result in liver damage [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lung ( Figure 3b) and liver (Figure 3c) lesions were regressed in this group when compared to Group II, no histopathological lesions were detected in the kidney, liver, and lung tissues of Group V and VI in which sepsis was not created and only low-dose and high-dose CR were administered. There are studies showing that the application of propolis in LPS-induced organ damage can preven histopathological lesions (Doğanyiğit et al, 2013;El-Mahalaway, Selim, & Mahboub, 2015;Ramadan, Soliman, Sawsan, Salwa & Abdel-Rahman, 2015).…”
Section: Histopathological Evaluationmentioning
confidence: 99%
“…Although there have not been established comprehensive protective mechanisms in different species so far, there is an ever-increasing evidence of curcumin-mediated ameliorative role in aflatoxicosis. Curcumin has been reported to demonstrate protective function in AFB1 inflicted damage to liver, kidneys, and overall growth parameters, mainly in ducks, chickens, and rodents [ 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ].…”
Section: Curcumin-mediated Afb1 Toxicity Control and Protective Mementioning
confidence: 99%